Memorializing, allegory and the rewriting of Nathaniel Hawthorne - Holman, Rupert (1998)
The thesis uses Hawthorne's interest in a scene of filial ambiguity, namely Samuel Johnson's penance to argue that Hawthorne's (re-) writing is characterised by a subversion of origins (both metaphysical and cultural). Complementing this argument, the thesis also attempts to show, with reference to texts by J. Hillis Miller, Jean-Francois Lyotard, Paul de Man and Maurice Blanchot, how deconstruction can offer new and important insights into Hawthorne's writing. Having outlined other important critical approaches (New Critical and New Historical) the thesis claims that, with its heightened sensitivity to the use of tropes, deconstruction is a particularly useful critical tool when it comes to reading Hawthorne. The thesis pays particularly close attention to two theoretical texts: Miller's Hawthorne and History: Defacing It and Lyotard's `Rewriting Modernity' and attempts to extend Miller's analysis (the only deconstructive text which refers directly to Hawthorne). This involves two movements. Firstly the thesis extends Miller's analysis by showing how it is echoed in the writings of de Man, Blanchot, and Lyotard. Secondly, the thesis refers to a wider selection of writings from Hawthorne's corpus (including writings from Twice-told Tales, Mosses From An Old Manse, The Snow-Image, `Alice Doane's Appeal', The Scarlet Letter, The Marble Faun, Our Old Home, the final `unfinished' manuscripts and diary and notebook entries). Using insights from these texts the thesis argues that Hawthorne rejects the idea that history involves the storing up of facts for future retrieval (a project which is aligned with memorialising). Hawthorne, it is argued, subverts this sense of memorialising by repeatedly drawing attention to an instability that contaminates each and every historical happening.